Physicochemical and functional characterization of a biosurfactant produced by Lactococcus lactis 53 - Rodrigues, L. R. (2006)
Isolation and identification of key components of the crude biosurfactant produced by Lactococcus lactis 53 was studied. Fractionation was achieved by hydrophobic interaction chromatography which allowed the isolation of a fraction rich in glycoproteins. Molecular (by Fourier transform infrared spectroscopy) and elemental compositions (by X-ray photoelectron spectroscopy) were determined. Critical micelle concentration achieved for the isolated fraction was 14 g/l, allowing for a surface tension value of 36 mJ/m². Moreover, the isolated fraction, stable to pH changes between 5 and 9, was found to be an anti-adhesive and antimicrobial agent against several bacterial and yeast strains isolated from explanted voice prostheses, even at low concentrations. Further purification steps should be carefully analyzed as each purification step will increase the costs and decreases the amounts of biosurfactants recovered.